2014
DOI: 10.1002/micr.22270
|View full text |Cite
|
Sign up to set email alerts
|

Influence of neck dissection and preoperative irradiation on microvascular head and neck reconstruction-Analysis of 853 cases

Abstract: Free tissue transfer in head and neck patients with previous irradiation and neck dissection is feasible and can be safely done. In addition, superficial temporal vessel could be the first choice in patients with previous radiotherapy and neck dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 23 publications
(28 reference statements)
2
21
1
Order By: Relevance
“…Factors, such as older age, smoking, and radiation, are nearly universal in patients undergoing free flap reconstruction in the head and neck and have not been demonstrated to have an impact on overall flap survival . However, given the myriad of potential defects, the fine nuances of flap selection and design, available recipient vessels, and the different types of flaps introduce factors that are not encountered in reconstruction of other anatomic regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors, such as older age, smoking, and radiation, are nearly universal in patients undergoing free flap reconstruction in the head and neck and have not been demonstrated to have an impact on overall flap survival . However, given the myriad of potential defects, the fine nuances of flap selection and design, available recipient vessels, and the different types of flaps introduce factors that are not encountered in reconstruction of other anatomic regions.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Factors, such as older age, smoking, and radiation, are nearly universal in patients undergoing free flap reconstruction in the head and neck and have not been demonstrated to have an impact on overall flap survival. [10][11][12] However, given the myriad of potential defects, the fine nuances of flap selection and design, available recipient vessels, and the different types of flaps introduce factors that are not encountered in reconstruction of other anatomic regions. Further, the literature is lacking in data that will alter clinical practice to improve outcomes, in particular, a knowledge gap exists regarding the true utility of different salvage techniques on improving flap survival and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Different options for recipient vessels for head and neck reconstruction including superior thyroid artery, facial artery, lingual artery, superficial temporal artery, and transverse cervical artery have been addressed . In this study, we have shown that the STA is appropriate for use of the “open‐Y” technique because it has several constant branches, including the infra‐hyoid, middle sternocleidomastoid, superior laryngeal, and the cricothyroid arteries.…”
Section: Discussionmentioning
confidence: 93%
“…20 Previous neck dissection and irradiation of the neck have a significant bearing on the availability of recipient vessels for free tissue transfer. 21 A careful review of previous operative notes is important to help determine the vascular status of the neck. Radiotherapy is associated with endothelial degeneration and necrosis, vessel lumen narrowing, and a prothrombotic environment 22 and there is a higher rate of complications and flap failure in those who were previously operated on or with irradiated necks.…”
Section: Preoperative Investigationsmentioning
confidence: 99%